Selection rationale for leakage monitoring in gas pipeline - A. D. Lebed; S. P. Glushko (Advanced Engineering Research, 2019)
Introduction. Efficient leak detection methods and gas flow metering are analyzed. The work objective is to select an automatic system of methods providing the improvement of the quality of leakage monitoring and gas flow metering in gas pipelines.Materials and Methods. The following techniques for detecting gas leakage in the pipeline are considered: according to the pressure profile, volume balance method, acoustic emission method, variable-pressure drop method on the forcing device, ultrasonic method.Research Results. The analysis shows that all techniques for monitoring leakage and gas flow are dependent on the environmental parameters. Therefore, an important task is to achieve independence of the measurement results from changes in the environmental parameters. In most flow meters, changes in density, pressure and temperature affect drastically the measurement results. An additional error that arises in this case can reach large values.